Acceptor-donor-acceptor type planar hole-transporting materials for efficient dopant-free perovskite solar cells. (2nd January 2018) - Kranthiraja, Kakaraparthi; Kwon, Haeun; Gal, Yeong-Soon; Lee, Jae Wook; Jin, Sung-Ho
ABSTRACT: Acceptor-donor-acceptor (A-D-A) type organic small molecule (SM-1) has been explored as an efficient dopant-free hole transporting material (HTM) to replace spiro-OMeTAD in the perovskite solar cells. High quality smooth, uniform, and hydrophobic SM-1 HTM can be readily deposited through solution casting without any external dopants. The highly compatible highest occupied molecular orbital level of −5.15 eV of SM-1 with respect to the perovskite valence band, along with intrinsically rich hole conductive nature effectively extracts holes from perovskite and thereby showed a reasonably high power conversion efficiency of 10.54%. Henceforth, the SM-1 based PSCs results successfully demonstrate the advancement of dopant-free PSCs through design engineering of planar A-D-A type conjugated small molecules.